Diagnostic accuracy of intraoperative CT-imaging in complex articular fractures: a cadaveric study - Luxenhofer, Miriam; Beisemann, Nils; Schnetzke, Marc; Vetter, Sven Y.; Grützner, Paul Alfred; Franke, Jochen; Keil, Holger (Scientific reports, 2020)
Anatomic reconstruction of articular fractures is one of the critical factors in later achieving good functional outcome. Intraoperative 3D imaging has been shown to offer better evaluation and therefore can significantly improve the results. The purpose of this study was to assess the difference between intraoperative three-dimensional fluoroscopy (3D) and intraoperative computed tomography (iCT) imaging regarding fracture reduction, implant placement and articular impressions in a distal humeral fracture model. AO type 13-B2 fracture pattern were created in upper extremity cadaver specimens. Articular step-offs, intra-articular screw placement and intraarticular impressions of different degrees of severity were created. All specimens had imaging performed. For each articular pattern 3D fluoroscopy in standard (3Ds) and high quality (3Dh) were performed (Arcadis Orbic, Siemens, Germany) as well as an intraoperative CT scan (iCT, Airo, Brainlab, Germany). Three observers evaluated all imaging studies regarding subjective and objective parameters. iCT is more precise than 3D fluoroscopic imaging for detection of articular impressions. Articular step-offs and intraarticular screw placement are similar for iCT and 3D. Subjective imaging quality is the highest for iCT and lowest for 3Ds. Intraoperative CT may be particularly useful in assessing articular impressions and providing a good subjective image quality for the surgeon.